Usefulness and limitations of the acute respiratory distress syndrome definitions in non-intubated patients. A narrative review - Zbiral, Martin; Weber, Maximilian; König, Sebastian; Kraft, Felix; Ullrich, Roman; Krenn, Katharina (Frontiers in Medicine, 2023)
According to the Berlin Definition of acute respiratory distress syndrome (ARDS), a positive end-expiratory pressure (PEEP) of at least 5 cmH2O is required to diagnose and grade ARDS. While the Berlin consensus statement specifically acknowledges the role of noninvasive ventilation (NIV) in mild ARDS, this stratification has traditionally presumed a mechanically ventilated patient in the context of moderate to severe ARDS. This may not accurately reflect today’s reality of clinical respiratory care. NIV and high-flow nasal cannula oxygen therapy (HFNO) have been used for managing of severe forms of acute hypoxemic respiratory failure with growing frequency, including in patients showing pathophysiological signs of ARDS. This became especially relevant during the COVID-19 pandemic. The levels of PEEP achieved with HFNO have been particularly controversial, and the exact FiO2 it achieves is subject to variability. Pinpointing the presence of ARDS in patients receiving HNFO and the severity in those receiving NIV therefore remains methodically problematic. This narrative review highlights the evolution of the ARDS definition in the context of noninvasive ventilatory support and provides an overview of the parallel development of definitions and ventilatory management of ARDS. It summarizes the methodology applied in clinical trials to classify ARDS in non-intubated patients and the respective consequences on treatment. As ARDS severity has significant therapeutic and prognostic consequences, and earlier treatment in non-intubated patients may be beneficial, closing this knowledge gap may ultimately be a relevant step to improve comparability in clinical trial design and outcomes.